2010
DOI: 10.1139/y10-065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of small doses of various drug vehicles on acetaminophen-induced liver injury

Abstract: The biological effects of drug vehicles are often overlooked, often leading to artifacts in acetaminophen-induced liver injury assessment. Therefore, we decided to investigate the effect of dimethylsulfoxide, dimethylformamide, propylene glycol, ethanol, and Tween 20 on acetaminophen-induced liver injury. C57BL/6 male mice received a particular drug vehicle (0.6 or 0.2 mL/kg, i.p.) 30 min before acetaminophen administration (300 mg/kg, i.p.). Control mice received vehicle alone. Liver injury was assessed by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…at the indicated doses in one of two metabolically inert vehicles: warm saline (mice) or 20% Tween-80 (rats). Saline and solutions of Tween are popular vehicles for the mouse and rat models, respectively, and have been shown to not interfere with APAP toxicity (Kelava et al, 2010). At various times, the animals were sacrificed by cervical dislocation (mice) or exsanguination (rats) under anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…at the indicated doses in one of two metabolically inert vehicles: warm saline (mice) or 20% Tween-80 (rats). Saline and solutions of Tween are popular vehicles for the mouse and rat models, respectively, and have been shown to not interfere with APAP toxicity (Kelava et al, 2010). At various times, the animals were sacrificed by cervical dislocation (mice) or exsanguination (rats) under anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, studies have shown that vehicles can be selected to improve the solubility and/or permeability of a drug or to target the drug to a specific disease site (Loftsson 1998;Porter et al 2007;Shin et al 2009;Hans and Lowman 2002;Liu et al 2011;Lee et al 2003). Vehicles have also been designed and formulated to mitigate unwanted toxicities associated with drugs that are considered highly toxic (Huo et al 2010;Uchino et al 2005;Kelava et al 2010). Vehicles offer toxicity relief in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, increased ROS formation during CI-WR has been reported to lead directly to apoptosis [42]. The protective effects of ROS scavengers, such as DMSO, have been well established in numerous tissues [39][40][41][43][44][45] and would explain the apparent beneficial effect of DMSO alone in preventing the Comparison between cell necrosis found in the IPRL and ORLT models. As evaluated by Trypan blue uptake, a similar large number of necrotic SECs was found in the centrilobular areas, using the IPRL and ORLT models, while less necrotic SECs were found in periportal areas using the ORLT model (upper panel).…”
Section: Discussionmentioning
confidence: 99%
“…There is only one study dealing with this CI-WR experimental condition [23], but the partial protective effect of CsA was only evaluated using CsA dissolved in dimethylformamide, an organic solvent known to have similar antioxidant properties to DMSO [45]. Unfortunately, no control group was included evaluating only the solvent, questioning seriously the relevance of reported data.…”
Section: Discussionmentioning
confidence: 99%